Hepatic Artery Pseudoaneurysm: A Life-Threatening Complication of Liver Transplantation - Parlak, Selcuk (J Belg Soc Radiol, 2015)
Hepatic artery pseudoaneurysm is a rare but serious complication following liver transplantation. A 50-year-old male patient with ulcerative colitis, sclerosing cholangitis, and end-stage liver disease underwent right lobe transplantation from a living donor. The patient was hospitalized because of impairment in liver function tests and massive pretibial edema three months after surgery. In color Doppler ultrasound and multidetector computed tomography, a pseudoaneurysm with peripheral large thrombus was detected at the anastomosis site extending anterior to the hepatic artery. The patient died as a result of unstable hemodynamic conditions.